Next-Generation Sequencing Methods to Determine the Accuracy of Retroviral Reverse Transcriptases: Advantages and Limitations - Javier Martínez del Río; Luis Menéndez-Arias (Viruses, 2025)
Retroviruses, like other RNA viruses, mutate at very high rates and exist as genetically heterogeneous populations. The error-prone activity of viral reverse transcriptase (RT) is largely responsible for the observed variability, most notably in HIV-1. In addition, RTs are widely used in biotechnology to detect RNAs and to clone expressed genes, among many other applications. The fidelity of retroviral RTs has been traditionally analyzed using enzymatic (gel-based) or reporter-based assays. However, these methods are laborious and have important limitations. The development of next-generation sequencing (NGS) technologies opened the possibility of obtaining reverse transcription error rates from a large number of sequences, although appropriate protocols had to be developed. In this review, we summarize the developments in this field that allowed the determination of RNA-dependent DNA synthesis error rates for different RTs (viral and non-viral), including methods such as PRIMER IDs, REP-SEQ, ARC-SEQ, CIR-SEQ, SMRT-SEQ and ROLL-SEQ. Their advantages and limitations are discussed. Complementary DNA (cDNA) synthesis error rates obtained in different studies, using RTs and RNAs of diverse origins, are presented and compared. Future improvements in methodological pipelines will be needed for the precise identification of mutations in the RNA template, including modified bases.